STUDYING MASCULINITY(IES) IN BOOKS ABOUT GIRLS - Harper, Helen (Canadian Journal of Education/Revue canadienne de l’éducation, 2007)
This study explored the nature and performance of masculinity portrayed in popular young adult novels featuring female protagonists. Although all had their limitations, the novels offered more complex renderings of gendered identity in the lives of female and male adolescent characters, addressed the effects of enforced traditional masculinity, and productively, if only momentarily, disrupted the connection between sex and gender in ways that allow for engagement with alternative notions of masculinity. Studying masculinity in these contemporary young adult novels about girls’ lives offers much for students and teachers to consider in analyzing masculinity and femininity in texts and in life. Key words: cross‐dressing, youth, literature, masculinity, femininity, adolescent novels L’étude porte sur la masculinité telle que représentée dans des romans populaires pour jeunes adultes mettant en scène des protagonistes de sexe féminin. Malgré les faiblesses de tous ces romans, ils présentent des descriptions relativement complexes de l’identité masculine et féminine à l’adolescence, tiennent compte des effets de la masculinité traditionnelle et réussissent, ne serait‐ce que momentanément, à ébranler le lien entre le sexe et le genre de manière à permettre la prise en compte d’autres notions de la masculinité. Ces romans contemporains pour adolescents sur la vie des filles offrent un matériau riche aux élèves et aux enseignants qui veulent réfléchir sur la masculinité et la féminité dans les textes et dans la vie. Mots clés : Travestisme, jeunesse, littérature, masculinité, féminité, romans pour adolescents